An exploration of the social roles of plants in the Bronze Age Aegean - Day, Joanna (Trinity College (Dublin, Ireland). Department of Classics, 2007)
This thesis explores the role of flowers in the Aegean world during the Bronze Age. The focus is on Minoan Crete in particular, but evidence from contemporary societies in the Cyclades, the Near East and Egypt is also utilised.
Keywords: Classics, Ph.D.; Ph.D. Trinity College Dublin